Ukraine and it's conformity in application with international standard for preventing the spread of narcotic drugs - Us, Olha (2021)
The purpose of the article is to study and established how the State of Ukraine has been able in combating the use of narcotic drugs in it's territory in conformity with those standard put in place by international law. The following methods were used in the article: dialectical; generalization and analysis; logical and semantic; methods of the results; historical and legal; comparative and legal. Examples of successful experience of some foreign countries in the field of prevention of drug trafficking are analyzed, as well as the possibility of introducing proven forms of one or another successful foreign experience in Ukraine is considered. The degree of negative impact of drug-related processes on the economy of states, on the general level of crime, as well as on the level of well-being of a particular state is analyzed. The conclusions of authoritative scientists are summarized that the quality of the processes, one way or another related to the prevention of the spread of drugs, depends on the success of the combination of various means of combating them. It is also emphasized that the assistance that Ukraine receives from developed western countries will play an important role, at least in the next few years.